2020
DOI: 10.1111/jcmm.16017
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β‐catenin signalling controls bile duct regeneration by regulating differentiation of ductular reaction cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…LGR5+ LPC expressed mostly the cholangiocyte marker KRT19 [13]. In line, ductular-reaction cells highly express LGR5 and could differentiate as KRT19 cholangiocytes in Lgr5-CreERT2 mouse model [27]. In contrast, LGR5+ LPC in human cirrhotic livers in our study co-expressed markers for hepatocytes rather than cholangiocytes, even in livers with strong ductular reactions.…”
Section: Discussionsupporting
confidence: 61%
“…LGR5+ LPC expressed mostly the cholangiocyte marker KRT19 [13]. In line, ductular-reaction cells highly express LGR5 and could differentiate as KRT19 cholangiocytes in Lgr5-CreERT2 mouse model [27]. In contrast, LGR5+ LPC in human cirrhotic livers in our study co-expressed markers for hepatocytes rather than cholangiocytes, even in livers with strong ductular reactions.…”
Section: Discussionsupporting
confidence: 61%
“…Recent findings have shown that progenitor stem‐like cells play a crucial role in biliary epithelium restoration and hepatocyte regeneration 40,41 . As progenitor cells express unique regenerative qualities and seem to be associated with liver tissue fibrosis, they have become an interesting target for the development of novel therapeutic options to tackle biliary injury 42,43 . With K7‐AI model 2.0, DR can be quantified precisely and reproducibly.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the 3,5‐diethoxycarbonyl‐1,4‐dihydrocollidine (DDC) diet in mice causes bile duct injury and induces ductular reaction cells expressing Leucine‐rich repeat‐containing G‐protein coupled receptor 5 (LGR5) and harboring a bipotent differentiation potential. [ 34 ] Furthermore, the employment of additional chronic injury model also assists in investigating the role of DKK3 in a liver resident stem cell compartment. [ 35 ] Specifically, Dkk3 loss leverages proliferation of hepatocytes and acinar cells after acute injury and attenuates chronic liver damage by expansion of the LGR5‐positive liver progenitor pool.…”
Section: Introductionmentioning
confidence: 99%